Compilation a Model of Professional Competencies of Educational Managers of Iran Program and Budget Organization - Zeynab Nazarzadeh Danak; Amirhossein Mahmoodi; Abbas Khorshidi (Iranian Journal of Educational Research)
Objective: The primary aim of the present investigation was to establish a model delineating the professional competencies exhibited by educational managers within the program and budget organization of Iran. Methods: The research employed a systematic methodology via  grounded theory, with the statistical population consisting of 16 experts or focal circles specializing in professional competencies. Data was gathered through interviews as the primary qualitative data collection method, and triangulation method (data consensus, researchers' consensus, theory consensus, methodology consensus) was utilized to validate and ensure the reliability of the measurement tool. To dissect the qualitative data, a systematic approach based on foundational data theory (Strauss and Corbin) was implemented through three phases of open, axial and selective coding. Results: The outcomes reveal that the principal dimensions of professional competencies among educational managers in the Iran program and budget organization encompass six dimensions: causal conditions, contextual conditions, intervening conditions, strategies, consequences, and central categories. Conclusions: The distinctive aspect of the current study lies in its development of a model illustrating the professional competencies of educational managers within Iran's program and budget organization through a qualitative lens.